2022
DOI: 10.1021/acsaem.2c01170
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Performance in 2D Technetium Dichalcogenides TcX2 (X = S, Se, or Te)

Abstract: In recent years, the search for alternative energy sources has been of major research interest, and one of the potential solutions is thermoelectricity. Moreover, studies on the emergence of transition-metal dichalcogenides (TMDs) have been unstoppable because of their unique properties. Among this group of materials, technetium-based TMDs (TcX 2 , where X = S, Se, or Te) are one of the least investigated materials. Using first-principles calculations, we systematically studied the structural stability and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…Among them, graphene, which is renowned for its exceptional electronic properties such as high electron mobility and remarkable mechanical strength, is the first 2D material discovered to have a nontrivial topological phenomenon . Since graphene was obtained experimentally, thousands of new 2D materials have been proposed, and many have been synthesized. Beyond graphene, the other reported two-dimensional topological materials possessing honeycomb structures are III–V buckled honeycombs, , MXenes, transition metal dichalcogenides (TMD), Janus materials, , ternary transition metal chalcogenides, , functionalized Bi/Sb, arsenene oxide, and RuClBr . Additionally, other 2D topological compounds in different structures such as copper sulfide, Zintl compounds, , half-Heusler compounds, and ilmenite oxidizes also exist.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, graphene, which is renowned for its exceptional electronic properties such as high electron mobility and remarkable mechanical strength, is the first 2D material discovered to have a nontrivial topological phenomenon . Since graphene was obtained experimentally, thousands of new 2D materials have been proposed, and many have been synthesized. Beyond graphene, the other reported two-dimensional topological materials possessing honeycomb structures are III–V buckled honeycombs, , MXenes, transition metal dichalcogenides (TMD), Janus materials, , ternary transition metal chalcogenides, , functionalized Bi/Sb, arsenene oxide, and RuClBr . Additionally, other 2D topological compounds in different structures such as copper sulfide, Zintl compounds, , half-Heusler compounds, and ilmenite oxidizes also exist.…”
Section: Introductionmentioning
confidence: 99%
“…These properties are crucial to the effective utilization and management of thermal energy as well as thermoelectrics [23]. Due to the quantum confinement effect, the decreased thermal conductivity and favorable electronic structure can be observed in some 2D systems, several studies have shown that the thermoelectric properties in monolayer materials are better than that of the corresponding bulk materials, such as TcTe 2 [24], CrSe 2 [25], α-PtO 2 [26] and so on. For the perovskites, bidimensionalization can improve the stability, the electronic structure characteristics, and thermoelectric transport properties, which is conducive to optimizing the thermoelectric performance by regulating the thermoelectric parameters.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, they found that SnS 2 nanosheets show a negative correlation between κ e and σ, indicating that the reduction in thickness can effectively improve its thermoelectric efficiency. Indeed, 2D materials, such as Janus monolayer (ML) WS-X (X = Se, Te) 22 and TcX 2 (X = S, Se, Te), 23 simultaneously deliver low lattice thermal conductivity and high ZT value. However, common 2D materials such as graphene (∼2000 W m −1 K −1 ), 24 MoS 2 (23.2−34.5 W m −1 K −1 ), 25 and phosphorene (24.3−83.5 W m −1 K −1 ) 26 possess high thermal conductivity, failing to meet the needs of thermoelectric applications.…”
Section: ■ Introductionmentioning
confidence: 99%